2009
DOI: 10.1002/jssc.200900341
|View full text |Cite
|
Sign up to set email alerts
|

CE‐LIF chiral separation of aspartic acid and glutamic acid enantiomers using human serum albumin and sodium cholate as dual selectors

Abstract: Sodium cholate (SC), beta-CD, hydroxypropyl (HP)-beta-CD, HSA, and the dual mixtures of them were evaluated for the analysis of aspartic acid (Asp) and glutamic acid (Glu) enantiomers fluorescently tagged with 5-(4,6-dichloro-s-triazin-2-ylamino) fluorescein (DTAF) by CE with LIF detection. Among the investigated chiral selectors and the dual selector systems, the dual selector systems of HSA and SC resulted to be the most useful chiral selectors allowing relatively high chiral resolution. Several experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…Wang et al have reported chiral separation of Glu and Asp using human serum albumin (HSA) and SC as the dual CSs. Since HSA and SC work as affinity ligand and pseudostationary phase, for enantioresolution, respectively, the amino acids are optically separated by both ACE and MEKC separation mechanisms [176]. Other attempts to use protein affinity ligands (BSA and avidin) have also demonstrated in the M-CEC and OT-CEC format, where native, PTH-and DNS-labeled amino acid racemates are successfully separated [177][178][179][180].…”
Section: Other Separation Modesmentioning
confidence: 98%
See 1 more Smart Citation
“…Wang et al have reported chiral separation of Glu and Asp using human serum albumin (HSA) and SC as the dual CSs. Since HSA and SC work as affinity ligand and pseudostationary phase, for enantioresolution, respectively, the amino acids are optically separated by both ACE and MEKC separation mechanisms [176]. Other attempts to use protein affinity ligands (BSA and avidin) have also demonstrated in the M-CEC and OT-CEC format, where native, PTH-and DNS-labeled amino acid racemates are successfully separated [177][178][179][180].…”
Section: Other Separation Modesmentioning
confidence: 98%
“…In the pharmaceutical applications, the CZE separation of Tyr enantiomers labeled with a chiral fluorescent tag in an amino acid oral solution [189], the CD-MEKC separation of Asp enantiomers [70] and the ACE/MEKC dual separation of Asp and Glu enantiomers in compound amino acid injections [176] have been reported. Cheng et al have developed a unique chiral analysis system for pharmaceuticals application by the coupling of fully automated flow injection with CD-MEKC for on-line derivatization and separation of amino acid enantiomers, respectively [70].…”
Section: Pharmaceuticalsmentioning
confidence: 99%
“…A paper by Wang et al . 45 underlines the importance of using dual systems to obtain a good chiral separation of Glu and Asp enantiomers. If the role of these two amino acids as major excitatory neurotransmitters in mammalian central nervous system 46 is well known, the observation that D ‐Asp levels are elevated in cerebrospinal fluid (CSF) and depressed in brain tissue of patients affected by Alzehimer's disease 47, 48 stimulated the development of reliable analytical methods for its accurate analysis in real samples.…”
Section: Enantioseparation By Mekcmentioning
confidence: 99%
“…D / L Glu and D / L Asp labelled with 5‐(4,6‐dichloro‐ s ‐triazin‐2‐ylamino) fluorescein (DTAF) were separated using an optimized dual selector systems containing sodium cholate and human serum albumin (HSA) in less than 10.5 min. The buffers required for DTAF–Asp enantiomers include 12 mM cholate, 8 mM sodium borate buffer (pH 8.9), 0.8% w/v HSA, and 10% v/v methanol; while for DTAF–Glu enantiomers, the buffer contains 12 mM cholate, 10 mM sodium borate buffer (pH 9.1), 1.6% w/v HSA, and 5% v/v methanol (capillary 50 μm id 62.5/50 cm, −25 kV) 86.…”
Section: Chiralitymentioning
confidence: 99%